Innovation and firm survival: the role of timing, funding, and networks - Gao, Ming (Nanyang Technological University, 2024)
As small- and medium-sized enterprises (SMEs) are often considered one of the crucial drivers of economic growth, innovation as a vital factor affecting SMEs’ success has attracted great attention in the academic community in the last few decades. It not only helps incumbents shore up their position but also enables new entrants to get access to the current market. However, innovation sometimes harnesses firms due to its inherent risk. There is a large body of literature that provides empirical evidence for the debate regarding the positive and negative links between firms’ innovation and survival. While many studies have discussed how innovation influences firms’ survival, little has been done to explore how this relationship is shaped by other factors. Therefore, researchers realized that attention should be turned to exploring heterogeneous issues or the factors that may affect the influence of innovation on firms’ survival. Among the factors, it was found that the timing of innovation is an important contributor to firms’ survival. Thus, the first research question that will be addressed is: does the timing of innovation influence SMEs’ subsequent survival? The grounding theories of organizations and organizational ecology, as well as insights from the liabilities of newness and smallness, are used to explain the influence of the timing of innovation on SMEs’ survival. The results suggest that there is a negative relationship between SMEs’ innovation in the early stage and their survival. This finding reveals that premature innovation is accompanied by the risk of exit. By contrast, engaging in innovation at a later stage when firms are more stabilized would be more beneficial to firm survival.